Keputusan Konsumen Yang Dipengaruhi Oleh Faktor-Faktor Dalam Membeli Produk Minuman Secara Online - Syaharani Pratiwi Salam; Asmungi Asmungi (Fakultas Teknik Universitas Cenderawasih, 2023)
The objective of this research is to determine the factors that influence consumer purchasing decisions to buy beverages online on marketplaces. The variables used are product, price, promotion, location, service quality, marketplace usability, and trust. The sample consists of 150 respondents. The Likert scale is used as the data collection model, and statistical analysis is conducted using multiple linear regression. After analyzing the data, this research has obtained results indicating that product (X1), price (X2), promotion (X3), location (X4), service quality (X5), marketplace usability (X6), and trust (X7) have a significant impact on buyer's decisions with a magnitude of 0.732 (73.2%), which means that all variables contribute and affect consumer purchase decisions by 73.2%, while the remaining 26.8% is attributed to other factors beyond the scope of this study. The results of the F-test analysis show that collectively, all variables significantly impact consumer purchasing decisions. The t-test analysis indicates that the research hypotheses for variables X1, X2, X6, and X7 significantly influence consumer purchase decisions, while variables X3, X4, and X5 do not significantly affect consumer decisions